Lipopeptide adjuvants for antibiotics and vaccines: the future step in the fight against multidrug-resistant and extensively drug-resistant pathogens - Chloé O. Sebilleau; Steven J. Sucheck (Exploration of Drug Science)
With the surge of antibiotic resistance in bacteria, the need for a larger arsenal of effective antibiotics and vaccines has drastically increased in the past decades. Antibiotics like vaccines can benefit from significant potentiation when used in combination with adjuvants. Antibiotic adjuvants can allow for gram-positive bacteria (GPB) specific treatments to be used against gram-negative bacteria (GNB) infections, with minimal antimicrobial resistance (AMR). In the case of vaccines, they allow for modulation and increase of the immune response. Lipopeptides are molecules of choice because of their ability to activate specific cell surface receptors, penetrate the outer membrane of GNB, safety and ease of synthesis. This review explores the recent developments in lipopeptide adjuvants for antibiotics and vaccines, providing a roadmap on how to develop adjuvants to efficiently combat AMR. After a brief overview of bacterial resistance, lipopeptide adjuvants for antibiotics and vaccines are discussed, providing insights into stability, sources, and delivery methods. Findings discussed in this review could be applied to the development of safer, more effective adjuvants, that could expand the use or repurpose current antibiotics or improve vaccination results in future clinical trials.